Aproveitamento de vísceras de tilápia para produção de biodiesel - Dias, Fernando Pedro (2009)
Stimulate the consumption of alternative energy translates into an undeniable factor in the development of responsible nations, aiming primarily to preserve and conserve the environment as well as the reductions of climate change the presents and futures. The biodiesel industry is a good option for market exploitation of oil extracted from the waste generated by industry of fish. Were collected and extracted oil from the offal of tilapia and this has been produced biodiesel using ethyl alcohol and the methyl alcohol transesterification reaction with NaOH. The extraction of hot indirect (cooking) was satisfactory conditions: 70 to 80ºC, atmospheric pressure, constant mechanical agitation and 45 minutes. The average yield of the extraction process of oil was 50, 3 ± 3,3% over the mass of the offal and the yield of biodiesel produced in both routes (ethanol and methanol) were 89,5 ± 0,3% and 96,9 ± 0,2% respectively. The parameters of certain biodiesel specification are within the limits required by the ANP. Fractionation of oil / fat tilapia resulted in two distinct fractions with the following percentages: 35,1 ± 0,3% of solid fraction (stearin) and 64,4 ± 0,0% of liquid fraction (olein). The fatty oil offal of tilapia were quantified using gas chromatography through the ethyl and methyl ester of fatty acids from biodiesel. The oil from fish offal of tilapia consists of the following fatty acids: 37,2% of oleic acid, 12,2% linoleic acid, 4,89% of palmitoleic acid, 1,79% linolenic acid and saturated with 28, 6% palmitic acid, 5,76% stearic acid, 3,57% of myristic acid in quantity majority